Yahoo奇摩 網頁搜尋

  1. expand the following expressions 1. (3x+2)(2-5x) =3x(2-5x)+2(2-5x) =6x-15x2+4-10x =-15x2-4x+4 2. [5x(x-3)(x+4...

  2. simplify the following expressions 1. (3x2–2x–3)–(x2–4x+1) = 3x2–2x–3–x2+4x&ndash...

  3. An algebraic expression of the form a + bx + cx^2 + dx^3 + ………….. in which a, b, c, d are ...like variable x) 現在將 term with the highest power 寫先, For quadratic expression , ax^2 + bx + c For cubic expression , ax^3 + bx^2 + cx + d For quartic expression ...

  4. ...x 2009 x 2010 which is a multiple of 10 ,so the units digit of the expression is 0. Method 2 ,1x2x3x...x2009x2010= 1 x 2 x 3 x 4 x 5 x 6 x 7...

  5. a. the product of 2 and the difference of x and 3 b. the difference of 2 times x and 3 c. the sum of 2 times the difference of x and 3 and 4 d. the difference of 2 times x and the sum of 3 and 4

  6. an expression is said to be independent of x iff (i.e. if and only if) the value of the expression remains unchanged while x changes its value. ...

  7. ...4pq+q² = -8pq+2q² 1b)Hence, find the value of the above expression when p=2 and q= -3. -8pq+2q² =-8(2)(-3)+2(2)² =48+8...

  8. Condition I: A and B are two consecutive numbers (B < A) So, A = B + 1 ─── (1) Condition II: Half of B exceeds one-fourth of A by 1...

  9. ... If x and y are irrational, which of the following expression must be irrational? A. 2x B. x + 2y C. 2xy D. All...

  10. ...(+,-,×,÷)and brackets, write down an expression with a result of 0 與算數運算 (+、 -、 ×、 ÷) 和托槽使用...